2020
DOI: 10.2147/ijn.s272750
|View full text |Cite
|
Sign up to set email alerts
|

<p>PLGA Nanoparticle Platform for Trans-Ocular Barrier to Enhance Drug Delivery: A Comparative Study Based on the Application of Oligosaccharides in the Outer Membrane of Carriers</p>

Abstract: The trans-ocular barrier is a key factor limiting the therapeutic efficacy of triamcinolone acetonide. We developed a poly(lactic-co-glycolic acid) nanoparticles (PLGA NPs) surface modified respectively with 2-hydroxypropyl-β-cyclodextrin (2-HP-β-CD), chitosan oligosaccharide and trehalose. Determination of the drug/nanoparticles interactions, characterization of the nanoparticles, in vivo ocular compatibility tests, comparisons of their corneal permeability and their pharmacokinetics in aqueous humor were car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 48 publications
(61 reference statements)
0
22
0
Order By: Relevance
“…Their size and surface potential can be enhanced, which selectively alters their membrane permeability. Jiang et al compared several commonly used PLGA copolymeric nanoparticles and identified that copolymers consisting of hydroxypropyl-β-cyclodextrin and PLGA had the highest entrapment efficiency and trans-ocular permeation [ 15 ]. PLGA can also be modified with the use of polyethylene glycol (PEG), to construct biocompatible nanoparticles with sustained drug release and high entrapment efficiency profiles.…”
Section: Overview Of Polymeric Nano-based Drug-delivery System (Dds)mentioning
confidence: 99%
See 1 more Smart Citation
“…Their size and surface potential can be enhanced, which selectively alters their membrane permeability. Jiang et al compared several commonly used PLGA copolymeric nanoparticles and identified that copolymers consisting of hydroxypropyl-β-cyclodextrin and PLGA had the highest entrapment efficiency and trans-ocular permeation [ 15 ]. PLGA can also be modified with the use of polyethylene glycol (PEG), to construct biocompatible nanoparticles with sustained drug release and high entrapment efficiency profiles.…”
Section: Overview Of Polymeric Nano-based Drug-delivery System (Dds)mentioning
confidence: 99%
“…This is especially important for glaucoma drugs such as brinzolamide, which has low solubility and thereby limits its therapeutic efficacy. Various studies have formulated PLGA-modified (Polylactic-co-glycolic acid) nanoparticles to have a sustained release of brinzolamide that significantly reduced IOP in animal models with minimal toxicity [ 15 , 46 , 47 ]. Song et al (2020) used a coaxial electrospray technique to coat PLGA nanoparticles with phosphatidylserine (PS), improving entrapment efficiency and corneal permeation with topical delivery of brinzolamide.…”
Section: Nano-based Dds For Glaucomamentioning
confidence: 99%
“…After the final observation, the animals were euthanized, and the eyeballs were stained with H&E for histopathological study. [53][54][55][56]…”
Section: Biocompatibility Studies In Rabbits Using Draize Testmentioning
confidence: 99%
“…The apparent corneal permeability coefficient (Papp) was calculated by the following equation where the ΔQ/Δt (μg/min) stands for the slope of the steady-state part of the cumulative permeation versus time graph, A stands for the effective corneal penetration area (cm 2 ) and C0 defined as the concentration of drug at the donor compartment (μg/mL). 26 𝑃 𝑎𝑝𝑝 = ∆𝑄 ∆𝑡.𝐴.𝐶 0 (Equation 4)…”
Section: Ex-vivo Permeation Of Drug Through Isolated Sheep Corneamentioning
confidence: 99%